Role of Cultural Similarity in Knowledge Transfer - LI, ZHENG (2018)
Since 2000s, although the global economic competition is still fierce, the relationship between enterprises shows a trend to transform from competition to cooperation. In such a business environment where competition and cooperation coexist, MNEs are constantly exploring new business operations, in which strategic alliance is the main means for MNEs to carry out FDI (Foreign Direct Investment) or cooperation between enterprises (especially scientific and technological enterprises). However, the success of knowledge transfer is influenced by many factors, among which cultural similarity is considered to be a crucial factor. How cultural similarity effects the knowledge transfer in vertical alliance business is still a blank in academic research of international business field and quite worth to have a deep exploration, which is what author is going to contribute to in this dissertation.